Reasons for the persistent incidence of venous thromboembolism - Heit, John A.; Ashrani, Aneel A.; Crusan, Daniel J.; McBane, Robert D.; Petterson, Tanya M.; Bailey, Kent R. (Thrombosis and Haemostasis, 2017)
Reasons for trends in venous thromboembolism (VTE) incidence are uncertain. It was our objective to determine VTE incidence trends and risk factor prevalence, and estimate population-attributable risk (PAR) trends for each risk factor. In a population-based cohort study of all residents of Olmsted County, Minnesota from 1981–2010, annual incidence rates were calculated using incident VTE cases as the numerator and age- and sex-specific Olmsted County population estimates as the denominator. Poisson regression models were used to assess the relationship of crude incidence rates to year of diagnosis, age at diagnosis, and sex. Trends in annual prevalence of major VTE risk factors were estimated using linear regression. Poisson regression with time-dependent risk factors (person-years approach) was used to model the entire population of Olmsted County and derive the PAR. The age- and sex-adjusted annual VTE incidence, 1981–2010, did not change significantly. Over the time period, 1988–2010, the prevalence of obesity, surgery, active cancer and leg paresis increased. Patient age, hospitalisation, surgery, cancer, trauma, leg paresis and nursing home confinement jointly accounted for 79 % of incident VTE; obesity accounted for 33 % of incident idiopathic VTE. The increasing prevalence of obesity, cancer and surgery accounted in part for the persistent VTE incidence. The PAR of active cancer and surgery, 1981–2010, significantly increased. In conclusion, almost 80 % of incident VTE events are attributable to known major VTE risk factors and one-third of incident idiopathic VTE events are attributable to obesity. Increasing surgery PAR suggests that concurrent efforts to prevent VTE may have been insufficient.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Venous thrombosis; pulmonary embolism; thrombophlebitis; phlebitis; epidemiology